1994
DOI: 10.1177/156482659401500414
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A Supplementation and Child Morbidity and Mortality in Developing Countries

Abstract: A meta-analysis of eight mortality trials indicates that improving the vitamin A status of children aged six months to five years reduced mortality rates by about 23% in populations with at least low prevalence of clinical signs of vitamin A deficiency. The observed effect of supplementation, described in terms of relative risk (RR), was RR =0.77 (95% confidence interval 0.68-0.88; p < .001) and did not differ by sex or age. However, the number of lives saved was greater at younger ages because of higher morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
271
2
5

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(282 citation statements)
references
References 2 publications
2
271
2
5
Order By: Relevance
“…Vitamin A deficiency impairs epithelial integrity and systemic immunity and increases the incidence and severity of infections during childhood. 6,8 Numerous studies in developing countries have shown that vitamin A supplementation reduces both mortality and morbidity from measles, 10,11,27 gastroenteritis and diarrhea, 10,11,13,27 malaria, 13 and HIV infections 8 and may decrease the number and length of hospitalizations and severity of illness events in at-risk populations. [12][13][14] From 15% to 92% of children in developing countries have serum retinol levels < 20 lg/dL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin A deficiency impairs epithelial integrity and systemic immunity and increases the incidence and severity of infections during childhood. 6,8 Numerous studies in developing countries have shown that vitamin A supplementation reduces both mortality and morbidity from measles, 10,11,27 gastroenteritis and diarrhea, 10,11,13,27 malaria, 13 and HIV infections 8 and may decrease the number and length of hospitalizations and severity of illness events in at-risk populations. [12][13][14] From 15% to 92% of children in developing countries have serum retinol levels < 20 lg/dL.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Vitamin A supplementation reduced mortality rates from infectious disease in community-based studies 10,11 and morbidity, particularly from measles, gastrointestinal diseases, and malaria. [8][9][10][11][12][13][14] Vitamin A supplementation also provides a benefit to the population in developing countries as a whole by reducing the number of visits for medical care and shortening the length of hospital stay. [12][13][14] We previously reported decreased serum vitamin A (retinol) and carotenoids in children with SCD.…”
mentioning
confidence: 99%
“…Standard 1 pupils were chosen as they had the bene t of at least 2 years of schooling, and after 10 years of age pubertal changes affect growth. 1,4 In KZN, attendance rate among primary schools is high, with 89.2% of children attending. 8…”
Section: Methodsmentioning
confidence: 99%
“…1 The prevalence of these public health problems in South African school children, their persistence beyond pre-school age and cost-effective strategies for control and prevention are poorly understood. [2][3][4] It has been recommended that vitamin A supplementation and de-worming should be part of a basic package of health services and incorporated into supplementary feeding programmes. 5 This has major policy and scal implications for ef cient use of health resources and the therapeutic ef cacy of the recommendations needs to be established under local conditions.…”
Section: Introductionmentioning
confidence: 99%
“…According to United Nations Administrative Committee on Coordination/subcommittee on nutrition (UN ACC/ SCN, The United Nations System Chief Executive's Board for Coordination at present), average availability in the world is 777 lg retinol equivalents (RE) per person per day (Beaton et al 1993) and minimum average requirements are around 250 lg RE per person per day (http://www.unsystem.org/scn/archives/ rwns02vol1/index.htm). RE is a concept introduced by the UN Food and Agriculture Organization (FAO)/WHO Expert Group in 1967 and is defined as 6 lg b-carotene or 11.9 lg of the other provitamin A carotenoids in food sources (World Health Organization 1967).…”
Section: Gm Crops With High Vitamin a Content: Golden Ricementioning
confidence: 99%